Analisis migran risen di sektor formal dan informal: Hasil Sakernas 2018 - Ary Fauziah Amini; Lilik Sugiharti; Neny Aditina; Yefin Amandri Meidika (Jurnal Ekonomi dan Bisnis, 2020)
The total population of migration in Indonesia has been on an upward trend in recent periods. In 1971, out of 100 population, 6 of them migrated, while in 1990 almost 10 out of 100 population migrated. Most migrants migrated to seek jobs . This study aims to analyze the participation of recent migrants in the labor market which is divided into two sectors, namely the formal and informal sectors. The data used in this study is the National Labor Force Survey (Sakernas) in February 2018 with the observation unit is recent migrants. number of observation units is 2,858 individuals spread across all districts/cities in Indonesia. By using the binary logistic regression analysis, the study finds that recent migrants are more likely to work in the formal sector than in the informal sector. Further, recent migrants who are younger, not married, have secondary and tertiary education, and have attended job training are more likely to participate in the formal sector.